Functions of lactate in the brain of rat with intracerebral hemorrhage evaluated with MRI/MRS and in vitro approaches. (2nd June 2020) - Liu, Yue; Yang, Shusheng; Cai, Erli; Lin, Li; Zeng, Peng; Nie, Binbin; Xu, Fuqiang; Tian, Qing; Wang, Jie
Abstract: Introduction: Lactate accumulation in the brain is caused by the anaerobic metabolism induced by ischemic damages, which always accompanies intracerebral hemorrhages (ICH). Our former findings showed that microglia's movement was always directly toward hemorrhagic center with the highest lactate concentration, and penumbra area has the largest density of compactly arrayed microglia. However, the relationship between microglia and lactate concentration has not been well documented. Methods: Cerebral hemorrhage model was successfully achieved by injecting collagenase VII (causing stabile localized bleeding) in CPu (striatum) of SD rats. Emodin was used as a potential therapeutic for ICH. The function of the lactate was examined with in vitro culture studies. Then, the effect of lactate on the proliferation, cell survival, migration, and phagocytosis property of microglia was investigated by in vitro culture studies. Results: Lactate accumulation was observed with in vivo MRS method, and its concentration was monitored during the recovery of ICH and treatment of emodin. Lactate concentration significantly increased in the core and penumbra regions of hemorrhagic foci, and it decreased after the treatment of emodin. The in vitro culture study was verified that lactate was beneficial for the proliferation, cell survival, migration, and phagocytosis property of the microglia. Conclusion: Results from in vitro verification study, investigations from the recovery of ICH, and treatment of emodin verify that lactate plays an important role during the recovery of ICH. This could provide a novel therapeutic approach for ICH.